Structural Basis of IL-1 Family Cytokine Signaling - Fields, James K.; Günther, Sebastian; Sundberg, Eric J. (Frontiers in Immunology, 2019)
Abstract Interleukin-1 (IL-1) family cytokines are key signaling molecules in both the innate and adaptive immune systems, mediating inflammation in response to a wide range of stimuli. The basic mechanism of signal initiation is a stepwise process in which an agonist cytokine binds its cognate receptor. Together, this cytokine-receptor complex recruits an often-common secondary receptor. Intracellularly, the Toll/IL-1 Receptor (TIR) domains of the two receptors are brought into close proximity, initiating an NF-κB signal transduction cascade. Due to the potent inflammatory response invoked by IL-1 family cytokines, several physiological mechanisms exist to inhibit IL-1 family signaling, including antagonist cytokines and decoy receptors. The numerous cytokines and receptors in the IL-1 superfamily are further classified into four subfamilies, dependent on their distinct cognate receptors – the IL-1, IL-33 and IL-36 subfamilies share IL-1RAcP as their secondary receptor, while IL-18 subfamily utilizes a distinct secondary receptor. Here, we describe how structural biology has informed our understanding of IL-1 family cytokine signaling, with a particular focus on molecular mechanisms of signaling complex formation and antagonism at the atomic level, as well as how these findings have advanced therapeutics to treat some chronic inflammatory diseases that are the result of dysregulated IL-1 signaling.